2016
DOI: 10.21474/ijar01/477
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Physico-Chemical Parameters of Water in Antiya Taal, Jhansi, India.

Abstract: Quality of water is an important criterion for evaluating the suitability of water for drinking and irrigation. The present study was carried out to determine the seasonal variations of physicochemical parameters in water samples from Antiya Taal, Jhansi city, India during August 2014 to May 2015. Seasonal variation of some physico-chemical parameters such as, temperature, pH, salinity, turbidity, conductivity, hardness, chloride contents, alkalinity, total solid, total suspended solid, total dissolved solid ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The higher values of pH were recorded in summer season and minimum at winter season. We can also say that alkaline pH may be due to release of bicarbonate and carbonate ions in to river body (Sharma and Gupta, 2004). Generally, in summer decomposition activities took place in higher level, hence this may be one of the reasons for high pH in the summer season.…”
Section: Resultsmentioning
confidence: 99%
“…The higher values of pH were recorded in summer season and minimum at winter season. We can also say that alkaline pH may be due to release of bicarbonate and carbonate ions in to river body (Sharma and Gupta, 2004). Generally, in summer decomposition activities took place in higher level, hence this may be one of the reasons for high pH in the summer season.…”
Section: Resultsmentioning
confidence: 99%
“…Water temperature either directly or indirectly affects numerous biotic and abiotic elements of an aquatic ecosystem (Singh, 2014). Water temperature data revealed the minimum mean value of temperatures was 17.3 ºC in site 1, while the maximum mean value of 21.0 ºC was recorded at site 11 and 12.…”
Section: Physico-chemical Parametersmentioning
confidence: 97%
“…6.8 to 8.2 is the ideal pH range for aquatic life. An important indication of the water quality and level of pollution in the watershed areas is the pH of an aquatic system (Kumar et al 2011; Singh 2014) [18,25] . The current study at Ghodha pachad Dam found that the minimum pH was 7.2 units in winter season and the maximum pH was 8.5 units in summer season (Table 1).…”
Section: Ph (Hydrogen Ions Concentrations)mentioning
confidence: 99%
“…Singh and Saha (1987) [26] found a higher level of alkalinity in the summer in a composite fish culture pond. Gupta et al (2016) [7] discovered a lower level of alkalinity in the winter while working on the Jamwa Ramgarh reservoir in Raipur, Rajasthan; Singh (2014) [25] discovered the same thing on the river Gomti (U.P.) in India.…”
Section: Total Alkalinity (Mg/l)mentioning
confidence: 99%